Biventricular unloading in patients with refractory cardiogenic shock. (1st November 2016) - Karatolios, Konstantinos; Chatzis, Georgios; Markus, Birgit; Luesebrink, Ulrich; Richter, Anette; Schieffer, Bernhard
Abstract: Background: Cardiogenic shock remains a clinical challenge with high mortality rate. Mechanical circulatory support (MCS) devices have become an integral component of the therapeutic armamentarium expanding the treatment options for refractory cardiogenic shock (RCS). Methods: We included all consecutive patients with biventricular unloading with Impella-2.5 and VA-ECMO admitted for RCS between October 2013 and March 2015. Outcome data included survival to discharge, bridging to VAD and 28-day mortality. Results: A total of 17 patients were included. Mean age was 63.3 ± 10.5 and 15 (88%) patients were male. RCS resulted from acute myocardial infarction in 14 (82%), acute myocarditis in 1 (6%) dilated cardiomyopathy in 2 (12%) patients. Mean SAPS II and SOFA score on admission was 74.7 ± 16.86 and 11.16 ± 1.79, respectively. Vasopressor doses and lactate levels were significantly decreased within 72 h on biventricular support (p = 0.025 for norepinephrine and p = 0.005 for lactate). Nine (53%) patients died while on support. Of the remaining 8 patients, 5 (29%) patients were weaned successfully and discharged in cardiac rehabilitation and 3 (18%) patients were successfully bridged to VAD. All 5 patients who were discharged to rehabilitation survived at day 28 after discharge, while 1 of 3 VAD patients died after VAD implantation, corresponding to an overall 28-day survival rate of 41%. Conclusions: Biventricular support with Impella-2.5 and VA-ECMO in patients with RCS is feasible and led to significant hemodynamic improvement and reduction of lactate levels. Despite high severity scores, ICU- and 28-day mortality rates were better than predicted.